Spillover Effects Of Palembang’s Economic Growth On Districts In South Sumatra - Nadari Nadari; Mukhlis Mukhlis; M. Subardin (Jurnal Pamator : Jurnal Ilmiah Universitas Trunojoyo, 2025)
This study aims to analyze the causality of economic growth of Palembang City which provides a spillover effect on districts / cities in South Sumatra Province. The data used is the Gross Regional Domestic Product (GRDP) at Constant Prices (ADHK) of Regency / City in South Sumatra consisting of Palembang City, Ogan Komering Ulu Regency, Muara Enim Regency, Prabumulih City, Pagar Alam City in the period 2001 - 2023. The analysis method used in this research is the Granger Causality Test. The results showed that there was a relationship between the economic growth of Palembang City and the economic growth of regencies / cities in South Sumatra, the relationship given was one-way. This means that the economic growth of Palembang City is able to have a spillover effect on economic growth in other districts / cities in South Sumatra, including Ogan Komering Ulu Regency, Prabumulih City, and Muara Enim Regency. The economic growth of Palembang City affects the economic growth of surrounding areas, this is because of the complex economic interactions realized through input output linkages that permeate various sectors, ranging from the manufacturing industry, services, trade, agriculture, mining, to crucial sectors such as education.